Sexual violence and armed conflict - Leatherman, Janie, 1959- (Cambridge ; Malden, MA : Polity, 2011)
"Every year, hundreds of thousands of people become victims of sexual violence in conflict zones around the world, most of them women and girls; in the Democratic Republic of Congo alone, approximately 200,000 have faced sexual violence since 1998, and those attacks continue to devastate Eastern Congo in particular, leading to the systematic collapse of safe space. This book offers a comprehensive analysis of the causes and consequences of, as well as responses to, sexual violence in contemporary armed conflict. It explores the functions and effects of wartime sexual violence as part of a global political economy of violence. To understand the motivations of the men (and occasionally women) who per petrate this violence, the book analyzes the role played by systemic and situational factors such as patriarchy and militarized masculinity in a tangled web of plunder and profit. Difficult questions of accountabi lity are tackled; in particular, the case of child soldiers, who often suffer a double victimization when forced to commit sexual atrocities a nd other crimes. The book concludes by looking at strategies of prevent ion and protection as well as an ethics of caring to support the rehabi litation of survivors and their reintegration into family and community life. Sexual violence in war has long been a taboo subject but, as thi s book shows, new and courageous steps are at last being taken--at both local and international levels--to end what has been called the "great est silence in history." "--P. [4] of cover.
Ending the silence -- Dimensions of sexual violence in conflict -- Sexual violence and the onset of armed conflict -- Seeking safe space -- Sexual violence and the global political economy of war -- From protection and accountability to an ethic of caring.
Includes bibliographical references and index.
Keywords: Women -- Crimes against; Children -- Crimes against; Women and war; Children and war; War and society; Sex crimes; War victims